2021
DOI: 10.1038/s41598-021-98460-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, epidemiology, autoantibody status, HLA haplotypes and genetic mechanisms of type 1 diabetes mellitus among children in Qatar

Abstract: To describe the clinical features, epidemiology, autoantibody status, HLA haplotypes and genetic mechanisms of type 1 diabetes mellitus (T1DM). Patients (0–18 years) with diabetes were recruited. Clinical data was collected, autoantibodies and c-peptide were measured. Whole Genome Sequencing was performed. Genomic data analysis was compared with the known genes linked with T1DM and HLA alleles were studied. 1096 patients had one or more antibody positivity. The incidence of T1DM in 2020 was 38.05 per 100,000 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
(42 reference statements)
1
6
0
1
Order By: Relevance
“…They used the PRG method to identify HLA alleles based on exome sequencing and found that HLA haplotypes DQA1*03:01:01G and DQB1*03:02:01G were common in Qatari children with T1DM. These variants have been previously reported in a study of Europeans, where they were in strong disequilibrium on linkage with HLA-DRB1*4 and were significant risk factors for T1DM development [30].…”
Section: Major Histocompatibility Complex (Hla) Locus: Population Asp...supporting
confidence: 60%
“…They used the PRG method to identify HLA alleles based on exome sequencing and found that HLA haplotypes DQA1*03:01:01G and DQB1*03:02:01G were common in Qatari children with T1DM. These variants have been previously reported in a study of Europeans, where they were in strong disequilibrium on linkage with HLA-DRB1*4 and were significant risk factors for T1DM development [30].…”
Section: Major Histocompatibility Complex (Hla) Locus: Population Asp...supporting
confidence: 60%
“…We could not follow up and confirm whether the HC who showed GADA positive status went on to develop T1D. The median disease duration of T1D patients in this study is 6 years, which is quite long and because GADA in sera is known to decrease with time, this could explain the lower prevalence of GADA in T1D patients in our population compared to other populations that have reported higher GADA prevalence 18,36–38 . It has been reported that GADA positivity is associated with an older age at T1D diagnosis and further GADA‐initiated autoimmunity was associated with longer disease duration 39,40 .…”
Section: Discussionmentioning
confidence: 59%
“…The median disease duration of T1D patients in this study is 6 years, which is quite long and because GADA in sera is known to decrease with time, this could explain the lower prevalence of GADA in T1D patients in our population compared to other populations that have reported higher GADA prevalence. 18,[36][37][38] It has been reported that GADA positivity is associated with an older age at T1D diagnosis and further GADA-initiated autoimmunity was associated with longer disease duration. 39,40 When we grouped our patients on the basis of age at T1D onset and disease duration, we found that prevalence of GADA was comparable in RD (disease duration <2 years) vs LS (≥2 years) T1D patients as well as in patients with age at onset <18 years vs ≥18 years.…”
Section: Discussionmentioning
confidence: 99%
“…This underscores an essential insight: existing whole genome and exome datasets, even if initially curated for different clinical or research purposes, can be adaptively repurposed. Such datasets then become invaluable secondary resources for endeavours in population genetics ( Gourraud et al, 2014 ), pharmacogenetics ( Dashti et al, 2022 ), and disease association studies ( Haris et al, 2021 ; Afyouni et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%